Efektivitas Penurunan Kadar Glukosa Darah Daun Lamtoro (Leucaena leucocephala L.) Pada Mencit Jantan (Mus muscullus L.) - Juliyanty Akuba; Endah Nurrohwinta Djuwarno; Faramita Hiola; Mahdalena Sy. Pakaya (State University of Gorontalo, 2022)
Diabetes mellitus (DM) is defined as a disease or metabolic disorder characterized by high blood glucose levels. The management of diabetes mellitus therapy in the community is diverse, ranging from synthetic drugs to herbal medicines. Many people assume that herbal medicines are relatively cheaper and safer compared to synthetic drugs. One of the plants commonly used as herbal medicine is Lamtoro. This research aimed to determine the effectiveness of Lamtoro leaves (LeucaenaleucocephalaL) on decreasing blood glucose levels on lab mice (Mus musculus L). This study used 27 male house mice divided into nine groups; each group consisted of three male house mice, i.e., glucose control (group I), negative control Na-CMC 1% w/v (group II), Positive control of chlamyd Gliben 1.56% w/v (group III), administered N-Hexan extract of Lamtoro leave 1% w/v (group IV), the extract of N-Heksan Lamtoro leaf 2.5% w/v (group V), the extract of N-Heksan Lamtoro leaf 5% w/v (group VI), ethanol extract of Lamtoro leaf 1% w/v (group VII), ethanol extract of Lamtoro leaf 2.5% b/v (group VIII), and ethanol extract of Lamtoro leaves 5% w/v (group IX). The results were analyzed using the One Way ANOVA test. It showed that N-Hexane and Ethanol extract of Lamtoro leaves with a concentration of 1% w/v, 2.5% w/v and 5% w/v was able to reduce the blood glucose levels. The extract which had the best activity in reducing blood glucose levels was found in ethanol extract 96% at a concentration of 5% w/v with a decrease in the percentage by 59%. This was because the 96% ethanol extract contained a number of secondary metabolite compounds, i.e., flavonoids, alkaloids and tannins as blood glucose levels reducer